The Role of Anti-Corruption Education in the Light of Aristotelian Concept of Akrasia: An Epistemic Inquiry into the Anti-corruption Initiatives in Kenya - Amukowa, Wycliffe; Gunga, Samson (MCSER-CEMAS-Sapienza University of Rome, 2013)
This paper undertakes an epistemic investigation of the efforts to combat corruption in Kenya in the light of Aristotle’s concept of Akrasia, and proposes a model for educational practice for the purpose of facilitating the fight against corruption. Akrasia is taken to mean a lack of command over self, leading one to act against one’s better judgment that one ought to choose virtue against vice
Keywords: Aristotle; Akrasia; Corruption; Ethics; Education; Kenya